2007
DOI: 10.1097/01.icl.0000250885.35316.85
|View full text |Cite
|
Sign up to set email alerts
|

Central Versus Paracentral Endothelial Cell Density Values in Relation to Duration of Soft Contact Lens Wear

Abstract: In morphometry of the corneal endothelium away from central sites, the history of contact lens wear must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In line with earlier conclusions, 35,36 it seems unlikely that an estimate of the COV from a single image can serve as a useful measure of the composition of the corneal endothelial cell layer, or as a reliable measure of changes after contact lens wear or surgery. One approach which has been applied to light microscopic images of stored corneas has been to use more than one image of the cell layer taken at slightly different locations, 29,40 although this approach might be questionable if there were substantial and predictable location‐dependent differences in the corneal endothelium 41 . While further studies to try to ascertain the reasons for the apparent dependence of the COV on the average cell area could be useful, further details of which cells are more likely to change (or stay the same) would seem to be a more logical goal for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In line with earlier conclusions, 35,36 it seems unlikely that an estimate of the COV from a single image can serve as a useful measure of the composition of the corneal endothelial cell layer, or as a reliable measure of changes after contact lens wear or surgery. One approach which has been applied to light microscopic images of stored corneas has been to use more than one image of the cell layer taken at slightly different locations, 29,40 although this approach might be questionable if there were substantial and predictable location‐dependent differences in the corneal endothelium 41 . While further studies to try to ascertain the reasons for the apparent dependence of the COV on the average cell area could be useful, further details of which cells are more likely to change (or stay the same) would seem to be a more logical goal for future research.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of Wiffen et al 22 has been subsequently confirmed by Doughty and Aakre, 23 who observed a mean central and mid-peripheral endothelial cell density of 2,747 and 2,954 cells/mm 2 , respectively, among 104 myopic contact lens wearers. They noted a net ratio of midperipheral endothelial cell density of 1.0768 : 1 (p < 0.001).…”
Section: Signs and Symptomsmentioning
confidence: 87%